Combinatorial Usage of Sumac Unriped Fruit Extract (Rhus Coriaria) and Tannic Acid Enhanced Synergistic Anti-Angiogenic Effect on Chick Chorioallantoic Membrane Assay - ÜNDER, DUYGU (ISTANBUL UNIV-CERRAHPASA, 2021)
Rhus coriaria (sumac) naturally grows worldwide and contains many phytochemicals. Tannic acid is frequently used for treating medical conditions. The aim of this study is to determine the synergistic effects of methanolic and acetonic extracts of Rhus coriaria's from unriped fruits in combination with tannic acid on angiogenesis by using the Chick Chorioallantoic Membrane (CAM) assay. The effects of methanol and acetone extracts of Sumac (MES and AES, respectively, at a final concentration of 5 mg/mL for both) and tannic acid (Tan 1.25 and 5 mg/mL) alone or in combination were examined for their effect on angiogenesis by applying the CAM assay. CAM assay results showed that AES is more effective than MES on suppressing angiogenesis. Tannic acid started to show antiangiogenic effects at the concentration of 5 mg/mL. When AES and tannic acid were used in combination at a dose of 5 mg/mL each, a very strong antiangiogenic effect was observed (score; 1.1 +/- 0.131, p<0.001). The combinatorial usage of AES and tannic acid may result in strong suppression of angiogenesis, an effect that is shown in this study for the first time. Based on this observation, combinatorial usage of sumac extracts and tannic acid could be promising as a new antiangiogenic therapy.
Keywords: Angiogenesis; chick chorioallantoic membrane assay; sumac; tannic acid; IN-VITRO; ANTIOXIDANT ACTIVITY; L.; RESVERATROL; CYTOTOXICITY; COMPOUND; PATHWAYS; QUALITY; GROWTH; DRUGS